PENYELESAIAN SENGKETA TAHAPAN PEMILIHAN UMUM KEPALA DAERAH DAN WAKIL KEPALA DAERAH MELALUI PENGADILAN TATA USAHA NEGARA - Jabaruddin Jabaruddin (Lakidende Law Review, 2022)
Settlement of disputes in regional head elections through the Lawsuit of the State Administrative Court is an appropriate legal action because the State administrative court has the authority to decide and adjudicate on stage disputes as regulated in the Supreme Court Circular Letter (SEMA) Number 07 of 2010 and legal consequences The decision of the Administrative Court in a dispute at the stage of the regional head and deputy regional head election to the election stages that have been carried out cannot be carried out by the KPU because the election has been completed on November 4, 2010. In addition, the State administrative decision does not have executive power because The only one authorized to participate in the plaintiff's election is the KPU, especially in the decision of the panel of judges at the Kendari State Administrative Court not to order the Southeast Sulawesi Provincial KPU to stop or cancel the ongoing stages and this is in line with the M's decision. the Constitutional Court which won the defendant in this case the Provincial KPU as the executor in this case the Central KPU commissioner.